Lightweight identity-based authentication protocol for wireless sensor networks. (2016) - Ouada, Farah-Sarah; Omar, Mawloud; Bouabdallah, Abdelmadjid; Tari, Abdelkamel
Wireless sensor network (WSN) is often deployed in hostile environments, which make it vulnerable to attacks. WSN comprises a large number of sensor nodes with different hardware abilities and functions. Due to the limited memory resources and energy constraints, complex security algorithms cannot be used in WSN. Hence, it is necessary to balance between security requirements and energy consumption. In this paper, we propose a lightweight public-key-based authentication protocol for WSNs. Our protocol uses identity-based encryption in order to lighten the energy consumption from the public-key certificate management. We have developed two variations of the proposed solution depending on the manner and when an attack should be detected. We perform an overall evaluation of our approach through simulations. The results indicate out performance of our approach in terms of energy consumption while providing effective security.